Literacy Workers or Competent Professionals : A Case Study - Vijaysimha, Indira (Voices of Teachers and Teacher Educators, 2018)
The paper presents a case study of how a well thought out teacher develop program can contribute positively towards innovative education of tribal children. The paper draws upon classroom observation of teacher’s practices, children’s reading writing and comprehension (pre, mid and post) in project schools and control schools and qualitative data from teacher and student interviews. By enabling teachers as professionals through professional development and not just training, it was possible to create an ecosystem where all stakeholders were invested in the education process. This study indicates that the successful implementation of the new practice results in improved reading ability, visible increase in student attendance and greater student interest towards school.